Demographic Prevalence of Drug Abuse in youth: Cases from the Surkhet District of Nepal - Pathak, Dhanush Chandra (Journal of Advanced Academic Research, 2017)
Any substance used in chemistry, dyeing, or any technical process or mix or adulterate with a drug, esp. a narcotic or prison. Drug abuse as a term used to indicate the excessive use of a drug, regardless of whether an individual has reached the point of true dependence on it, or not. The main objective of this study is to identify the demographic prevalence of drug abuse among youth in Surkhet district. Quantitative research method was used to draw the data from 29 respondents of Birendranagar valley of Nepal. Simple Random sampling technique was used to select the respondents. Frequency table was generated for quantitative data. Demographic factors and pattern were taken to identify the demographic prevalence of drug abuse. Demographic factors had covered age, family, caste/ethnicity, education, occupation and marital status. Likely pattern factors had covered place where they use drug, what types of drug they use and with whom they use drug. Among them, majority respondents reported they use mostly drug use age is between 21 - 25. Likewise Brahmin/Chhetri Caste and ethnicity used more drug to compare others caste. Equally more prevalence of drug use can see in Nuclear Family.Journal of Advanced Academic Research Vol. 3, No. 2, 2016, Page: 82-91